Bright near-infrared chemiluminescent dyes: Phthalhydrazides conjugated with fluorescent BODIPYs. (July 2020) - Li, Guanglei; Hirano, Takashi; Yamada, Koji
Abstract: A series of phthalhydrazides conjugated with NIR fluorescent BODIPY dyes were synthesized (three steps, overall yields 68–83%) and found to show strong NIR chemiluminescence (CL) with maxima in the range of 670–736 nm. One of these showed a CL quantum yield reaching 8.4 times higher than that of luminol. Tuning of the fluorescence band of the BODIPY unit directly leads to a red-shifted CL, developing a strategy for designing NIR chemiluminogens. Graphical abstract: Image 1